1961
DOI: 10.1111/j.2153-3490.1961.tb00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Cloud Patterns revealed by Tiros I

Abstract: In this report some satellite (TIROS I) photographs of cellular cloud patterns are related to conventional meteorological observations. These cellular patterns occurred at the top of convective layers which were heated from below; and through which there was little vertical variation in wind velocity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0

Year Published

1963
1963
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 10 publications
3
22
0
Order By: Relevance
“…3, the size of cloud element was fairly large and its height reached 5 km. Therefore, this cloud distribution is the same in size as those of Benard's cell type cloud distributions in satellite pictures which were reported by Krueger andFritz (1961), Hubert (1966) and Hardy (1968). However because our ring-shaped cloud distribution was isolated near the periphery of the convergence zone, it is considered that it was produced in the same mechanism as the several ring-shaped low-level cumulus cloud distribution.…”
Section: The Ring-shaped Clouds Over the Gulf Of Siamsupporting
confidence: 83%
See 1 more Smart Citation
“…3, the size of cloud element was fairly large and its height reached 5 km. Therefore, this cloud distribution is the same in size as those of Benard's cell type cloud distributions in satellite pictures which were reported by Krueger andFritz (1961), Hubert (1966) and Hardy (1968). However because our ring-shaped cloud distribution was isolated near the periphery of the convergence zone, it is considered that it was produced in the same mechanism as the several ring-shaped low-level cumulus cloud distribution.…”
Section: The Ring-shaped Clouds Over the Gulf Of Siamsupporting
confidence: 83%
“…These cloud patterns of ring-shape perhaps show a sort of convective cells with descending motion in the center and ascending Recently many ring-shaped cloud distributions were observed in satellite pictures. Krueger and Fritz (1961) reported that ring-shaped cellular patterns observed by a meteorological satellite had sizes of 30 to 50 miles in the diameter, and the patterns were formed below an inversion layer at a height of about 5000 ft (about 1.5 km). The size of the rings and the condition of the inversion were very similar to those of the present case.…”
Section: The Ring-shaped Clouds Over the Gulf Of Siammentioning
confidence: 99%
“…The dimensionless number, a, defined to represent the ratio as a=kd where d is the depth of layer and k is the horizontal wave number, ranges from 2.22 to 3.12 for a Benard cell as shown by the laboratory experiments and the theories, but it is of the order of 10-1 or 10-2 for the atmospheric cellular convection, (Krueger and Fritz, 1961).…”
Section: Introductionmentioning
confidence: 99%
“…1, which show that these POCs are coherent, long lived (the images span 16.5 h), and embedded in regions of relatively small values of AT . The longevity and coherence of POCs has attracted the attention of satellite meteorologists, with observational examples of POC-like features dating to the beginning of the satellite record (e.g., Krueger and Fritz 1961;Davies and Garay 2003;Garay et al 2004). Low values of A TB can be accounted for by a reduction in the cloud optical depth from values of 15 to unity (which is not consistent with the earlymorning visible imagery), or by changes in the effective radius from 6 to 12 /nm for a cloud with a fixed optical depth of 15 (e.g., Fig.…”
mentioning
confidence: 99%